OTONOMI DAERAH DALAM PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR DIKOTA SUNGAI PENUH TAHUN 2019: Herlinda - M.Si, Herlinda, (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2020)
This research took place at the office of the River City Regional Development Planning Agency (BAPPEDA). The purpose of this research is to find out how regional autonomy is in implementing infrastructure development in Sungai Penuh City. The approach taken in this research is qualitative. The number of informants was 7 people. Techniques and data collection tools in this study were interviews, observation, and documentation study. The unit of analysis is the Institute. The institution in this research is the regional development planning agency for Sungai Penuh City. The results show that the infrastructure development in Sungai Penuh City has been carried out by the regional government, however, the local government of Sungai Penuh City is not efficient enough in carrying out infrastructure development in the Sungai Penuh city. Because there are several roads in the Sungai Penuh city area that are still damaged. The weak planning factor in Sungai Penuh city is the natural resource factor, the funding factor, because the land availability in the Sungai Penuh city area is not sufficient, which is. The local government of Sungai Penuh City must be able to control the results of natural wealth so that regional revenue or revenue increases.